PERAN GURU DALAM MEMBENTUK KARAKTER KEMANDIRIAN SISWA KELAS I SD NEGERI 1 KEDALON WONOSOBO - Aulia, Adinda Nurani; Komalasari, Mahilda Dea (Jurnal PGSD Indonesia, 2022)
This study aims to describe the teacher’s role for the character building of student’s independence in the first grade in SD Negeri 1 Kedalon Wonosobo. This research use qualitative method for collecting the data using observation, interviews, and documentation. Secondary data was analyzed by using qualitative analysis technique. Examination of the validity of the data used triangulation techniques and triangulation of sources. Interviews were conducted on principals, the teacher of grade one, and  the student who in the grade one with the aim of obtaining data and information about the teacher's role in shaping the independent character of students in frist grade at SD Negeri Kedalon Wonosobo.The results of the research on the role of teachers in the character building of students who in the grade one at SD Negeri 1 Kedalon Wonosobo, teachers can shape the character of students' independence because , the teacher who got the responsibility to teach them or who got their own class, it can make a deal directly with their students and have a longer intensity of meetings with students when compared to principals and other educators. The teacher plays a role in directing and guiding students so that they have maturity in speaking or acting through words and actions. Teachers try to be able to guard and enforce discipline, both to themselves, students, and others. The teacher guides them to learn, to understand, and to solve the problems with themself                                                                                            Keyword : character education, roles of teachers, students independence